Research into the Mechanical Tillage Regulation Mechanisms of the Soil Structure in Black Soil Paddy Fields - Qiuju Wang; Bingqi Bai; Yuping Liu; Baoguang Wu; Jingyang Li; Jiahe Zou (Agriculture)
This study investigated the impact of the response mechanism of tillage construction on paddy yield in black soil fields by adopting four mechanical tillage techniques, namely, rotary tillage (RT), shallow plowing (SP), deep plowing (DP), and culvert pipe drainage (CD), to solve the problems associated with the reduction in the effective tillage layer in black soil paddy fields, as well as the poor quality and low yield of paddy rice. The results showed that SP, DP, and CD techniques were able to increase the rice yield and improve the effective tillage layer of the soil and the soil structure. Among them, DP had the most obvious effect, compared with traditional RT; the fast-acting N was 37.27 mg/kg higher in the 20–30 cm soil layer, and the soil solid phase decreased by 1.86–3.90% in the soil tripartite ratio. The soil bulk density of DP in the 10–20 cm soil layer decreased by 0.08 g/cm3, and, in the 20–30 cm soil layer, it decreased by 0.03 g/cm3. These physicochemical properties promoted the development and growth of roots and increased the growth of the root system by 6.53–16.33%, with the yield also increased by up to 9.81%. The CD technique could improve paddy field drainage and increase crop yields. This study combines four mechanical tillage techniques and proposes a mechanism of tillage construction from soil structure improvement to soil physicochemical property enhancement, and then to root system and yield enhancement. This mechanism may help to guide the implementation of mechanical tillage methods in paddy fields, which will provide important insights for future agricultural practices.